2020
DOI: 10.1155/2020/8721536
|View full text |Cite
|
Sign up to set email alerts
|

Association between LXR-α and ABCA1 Gene Polymorphisms and the Risk of Diabetic Kidney Disease in Patients with Type 2 Diabetes Mellitus in a Chinese Han Population

Abstract: We designed a case-control study and selected LXR-α rs7120118 C>T and ABCA1 rs2230806 A>G polymorphisms to determine the correlation between these polymorphisms and diabetic kidney disease (DKD) susceptibility in a Chinese Han population. Three hundred DKD patients and 346 type 2 diabetes mellitus (DM) patients without kidney disease were recruited. Our results showed that rs7120118 was associated with DKD (genotype, P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…One author discovered a novel variation in the ABCA1 gene, exon 14, in individuals with low HDL-C [ 27 ]. In addition, previous studies have reported a correlation between ABCA1 polymorphisms and the onset of diabetes and its complications [ 23 , 28 , 29 ]. Wang et al demonstrated a significant association of variant I883M in genetic models (AA vs. GG = p -value 0.010 and recessive p -value 0.011) with coronary heart disease [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…One author discovered a novel variation in the ABCA1 gene, exon 14, in individuals with low HDL-C [ 27 ]. In addition, previous studies have reported a correlation between ABCA1 polymorphisms and the onset of diabetes and its complications [ 23 , 28 , 29 ]. Wang et al demonstrated a significant association of variant I883M in genetic models (AA vs. GG = p -value 0.010 and recessive p -value 0.011) with coronary heart disease [ 30 ].…”
Section: Discussionmentioning
confidence: 99%